Compatibility-based selection of native fungi from oil palm empty fruit bunches for potential consortium development - NURHAIDA WIDIANI; BAMBANG IRAWAN; ROCHMAH AGUSTRINA; ANDI SETIAWAN (Asian Journal of Agriculture, 2026)
Abstract. Widiani N, Irawan B, Agustrina R, Setiawan A. 2026. Compatibility-based selection of native fungi from oil palm empty fruit bunches for potential consortium development. Asian J Agric 10 (1): g100169. https://doi.org/10.13057/asianjagric/g100169. Oil palm empty fruit bunches (EFB) are an abundant lignocellulosic biomass in tropical agroecosystems but remain underutilized due to their recalcitrant structure and slow natural decomposition. This study aimed to isolate native fungal strains from EFB and evaluate their compatibility as a basis for selecting candidates for microbial consortium development. Twelve fungal isolates were successfully obtained and morphologically characterized, predominantly belonging to the genus Aspergillus, with representatives of Penicillium and Mucor. Interactions among isolates were evaluated using a dual culture assay, revealing diverse compatibility patterns. Of the 50 pairings evaluated, 32% were classified as compatible, 24% as partially compatible, and 44% as incompatible, indicating that antagonistic interactions were prevalent among the isolates. To further investigate interaction dynamics, compatibility data were analyzed using Cooperativeness Scoring (CS), heatmap visualization, and network analysis. These approaches enabled a quantitative and structural assessment of interaction patterns, demonstrating that compatibility among isolates is selective rather than universal. Isolates such as BKR10, BKR2, and BKR3 showed relatively high compatibility and central positions within the interaction network, indicating their potential as candidates for consortium development based solely on compatibility metrics. However, it should be noted that this study was limited to in vitro interaction assays, and functional lignocellulose degradation was not evaluated. Therefore, the identified isolates should be regarded as preliminary candidates that require further functional validation. This study provides a systematic framework for compatibility-based selection of native fungal isolates associated with EFB.